PERANCANGAN SCIENCE CORNER (SCI-CO) SEBAGAI MEDIA BANTU VISUAL IMAGE BAGI GURU TK PGRI PALATTAE - Syaifullah, Adji; Akbar Asfar, Andi Muhamad Iqbal; Taufan Asfar, Andi Muhammad Irfan; F.A, A Nurannisa; Marlina, Marlina; Nurjannah, Sitti (Universitas Ahmad Dahlan, 2020)
It is currently endeavored to try to learn science learning from an early age to children, especially in kindergarten. Learning is directed towards creative and critical thinking that is able to direct children's high order thinking skills. The community service program with the PKM-M scheme was carried out at TK PGRI, Palattae Village, Bone Regency regarding the problems of teachers as partners in teaching science in the classroom to make it easier and more interactive through the design of a science corner (Sci-Co). This service was carried out in three main stages, namely counseling, design, and dissemination of the Sci-Co design. Learning using Sci-Co will be able to make children more critical and able to analyze events or phenomena that are often encountered in a child's environment, such as rain. Even though this program is conducted online, it is able to build teachers' skills in presenting Sci-Co in a simple way, the result of the teacher's own creativity with less than one week of processing time at the same time the teacher claims that this Sci-Co will help him accommodate children's knowledge in learning so that it is more meaningful less than one hour.